2016
DOI: 10.1051/0004-6361/201527235
|View full text |Cite
|
Sign up to set email alerts
|

The role of binaries in the enrichment of the early Galactic halo

Abstract: Context. The detailed composition of most metal-poor halo stars has been found to be very uniform. However, a fraction of 20−70% (increasing with decreasing metallicity) exhibit dramatic enhancements in their abundances of carbon; these are the so-called carbonenhanced metal-poor (CEMP) stars. A key question for Galactic chemical evolution models is whether this non-standard composition reflects that of the stellar natal clouds or is due to local, post-birth mass transfer of chemically processed material from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
110
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(123 citation statements)
references
References 109 publications
13
110
0
Order By: Relevance
“…Of the nine stars known with [Fe/H] ≤ −4.5, seven are CEMP-no stars (Placco et al 2014b;Bonifacio et al 2015;Frebel & Norris 2015), suggesting that C was already produced and enriched in the very first stellar generations. Their low binary frequency (Starkenburg et al 2014;Hansen et al 2016a), ∼17 ± 5%, consistent with that of halo stars with normal carbon content, and their lack of s-process-element abundance signatures makes a local AGB binary companion an unlikely source of their C excess, so another production site must be found.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Of the nine stars known with [Fe/H] ≤ −4.5, seven are CEMP-no stars (Placco et al 2014b;Bonifacio et al 2015;Frebel & Norris 2015), suggesting that C was already produced and enriched in the very first stellar generations. Their low binary frequency (Starkenburg et al 2014;Hansen et al 2016a), ∼17 ± 5%, consistent with that of halo stars with normal carbon content, and their lack of s-process-element abundance signatures makes a local AGB binary companion an unlikely source of their C excess, so another production site must be found.…”
Section: Introductionmentioning
confidence: 72%
“…Carollo et al (2014) presented indications that the CEMP-s stars are preferentially associated with the inner-halo population, while the CEMP-no stars are associated with the outer-halo population. Based on these, and other recent results (see, e.g., Ito et al 2013;Placco et al 2014a;Hansen et al 2016a), it is becoming increasingly clear that the CEMP-no stars may well be bona fide second-generation stars, born from an interstellar medium (ISM) polluted with the nucleosynthetic products of the very first stars.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Hansen et al (2011) first showed that the enhancement of r-process elements observed in a small fraction (3-5%) of VMP and EMP stars is not causally connected to membership in a binary system, this conclusion was confirmed and further strengthened in Paper I of this series (Hansen et al 2015b). Paper II (Hansen et al 2016) examined the same question for the class of CEMP-no stars and found that only 17 ± 9% (4 of 24) of their programme stars were binaries; this percentage is identical to the binary frequency found in metal-poor red giants. The present Paper III addresses the extent to which binaries may play a role in the origin of CEMP-s and CEMP-r/s stars, using the same approach.…”
Section: Introductionmentioning
confidence: 86%
“…The great majority of the former can be accounted for by scenarios involving transfer of enriched material from a binary companion that has passed through the asymptotic giantbranch (AGB) stage of evolution. The origin of the latter has still not been identified with certainty, but their binary frequency is not higher than among metal-poor giants in general (see Paper II of this series, Hansen et al 2016). As discussed there, a number of lines of evidence strongly suggest that the CEMP-no stars contain the nucleosynthesis products of the very first stars born in the Universe, i.e., that they are bona-fide second-generation stars.…”
Section: Introductionmentioning
confidence: 94%